Foreword - Vol 7 - Durrer, Victoria; FitzGibbon, Ali; Collins, Pat; Kelly, Marie (Irish Journal of Arts Management and Cultural Policy, 2020)
The introduction to Volume 7 of the Irish Journal of Arts Management & Cultural Policy reflects on the importance of voices from practice in this issue and the changing conditions Covid-19 has brought the sector.